Pertumbuhan Bibit Kopi Robusta (Coffea canephora Pierre) dengan Pemberian Beberapa Jenis Kompos - Ali, Muhammad; Khoiri, M. Amrul; Rachim, Kamalia (Jurnal Agro Teknologi Tropika, 2015)
The quality of seedling determines the growth and the productivity of plants in the field seedling. Optimum growthof seedling can be obtained through good nursery system. The physical, chemical and biological properties of nurserymedium can be improved by application of organic fertilizer, such as compost. This study aims to the effect of severaltypes of compost and get best compost dosage in inducing seedlings of Robusta coffee (Coffea canephora Pierre).Research has been conducted experimentally using a completely randomized design (CRD) with 5 treatments and 3replications. Each experimental unit consisted of 3 seedlings where 2 seedlings taken as sample. Data were analyzedstatistically using analysis of variance and means were tested by Duncanâs New Multiple Range Test at 5% level.Parameters observed were the increase of plant height (cm), the leaf number, leaf area, stem circle (cm) and the ratio ofthe root crown. The results indicated that the application of some compost affected the increase of seedling height, theleaf number and leaf area. Trichokompos gave the better seedling height and leaf number comparing to other compost.